2019
DOI: 10.1126/scitranslmed.aau7975
|View full text |Cite
|
Sign up to set email alerts
|

An engineered E. coli Nissle improves hyperammonemia and survival in mice and shows dose-dependent exposure in healthy humans

Abstract: The intestine is a major source of systemic ammonia (NH3); thus, capturing part of gut NH3 may mitigate disease symptoms in conditions of hyperammonemia such as urea cycle disorders and hepatic encephalopathy. As an approach to the lowering of blood ammonia arising from the intestine, we engineered the orally delivered probiotic Escherichia coli Nissle 1917 to create strain SYNB1020 that converts NH3 to l-arginine (l-arg). We up-regulated arginine biosynthesis in SYNB1020 by deleting a negative regulator of l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
222
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(229 citation statements)
references
References 90 publications
(103 reference statements)
7
222
0
Order By: Relevance
“…Fecal metabolomics has been focused on revealing changes in metabolites and metabolic pathways in diseases [36,42,43]. Thus, we performed metabolomics analysis of fecal samples to investigate changes in metabolite levels and metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal metabolomics has been focused on revealing changes in metabolites and metabolic pathways in diseases [36,42,43]. Thus, we performed metabolomics analysis of fecal samples to investigate changes in metabolite levels and metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered bacterial therapeutics possess a potential advantage over alternative microbiota-directed therapeutic approaches, such as fecal microbiota transplants or defined consortia of naturally occurring species, in that genetic engineering can confer functions that are not expressed by the endogenous microbiota. Engineered LBPs can be designed to perform natural biological processes, such as the assimilation of ammonia into amino acids, at significantly increased rates 14 and to produce effectors that are not native to bacteria, including human proteins 16 . Functions encoded by engineered bacteria also have potential for the treatment of inborn errors of metabolism (IEMs) present in the host, such as phenylketonuria (PKU) 54 .…”
Section: Design Of Engineered Therapeutic Strains For the Human Gutmentioning
confidence: 99%
“…In the United States, recombinant LBPs are regulated by the Food and Drug Administration (FDA) through the Center for Biologics Evaluation and Research (CBER). While there have been numerous probiotics approved as nutritional supplements and some engineered bacterial strains have been studied in the clinic [14][15][16] , the FDA has not approved a live biotherapeutic product for medicinal use to date. In 2016, the FDA issued a guidance document describing the regulatory considerations for conducting clinical trials with LBPs 10 .…”
mentioning
confidence: 99%
“…We focus on the probiotic Escherichia coli Nissle 1917 (EcN), an E. coli clade B2 commensal ( Figure S1). EcN has a long history of use in humans (Westendorf et al, 2005), has demonstrated efficacy against inflammatory bowel disease (Scaldaferri et al, 2016), and has been gaining increased attention as a chassis for engineered function (Hwang et al, 2017;Isabella et al, 2018;Kurtz et al, 2019;Palmer et al, 2018). We expected several factors to drive adaptation of EcN in the mouse gut.…”
Section: Introductionmentioning
confidence: 99%